FORMATION OF LEADERSHIP CHARACTER THROUGH KI HADJAR DEWANTARA’S EDUCATIONAL PHILOSOPHY IN THE CONTEXT OF ANTI CORRUPTION - Ummi Faizah; Nasikhin; Fihris; Ratna Muthia (Publikasi Inspirasi Indonesia, 2025)
This research aims to explore and analyze the role of Ki Hadjar Dewantara's educational philosophy as a foundation in shaping the character of anti-corruption leadership among the younger generation. The main focus of the research is to explore moral values such as honesty, responsibility, exemplary, and mutual cooperation contained in Ki Hadjar Dewantara's teachings, and how these values can be applied in formal and non-formal education environments to foster leadership attitudes with integrity. The research method uses a qualitative approach with a literature review design, where data is obtained through documentation studies and synthesis of literature from various sources such as books, journals, and official documents. Data analysis techniques refer to the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing, with data validity strengthened through source triangulation and member checking. The most important finding in this study is the relevance of Ki Hadjar Dewantara's principles, such as “tut wuri handayani,” “ing ngarso sung tuladha,” and “among,” in creating young leaders who are transparent, responsible, and dedicated to society. These principles can be implemented through exemplary learning methods, character education programs, and non-formal activities such as fundraising or leadership training. The contribution of this research lies in the development of a theoretical framework and the development of theoretical frameworks.